2022
DOI: 10.21037/atm-22-955
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia enhances the efficacy of chemotherapeutic drugs in heat-sensitive cells through interfering with DNA damage repair

Abstract: Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to be clinically effective, but the mechanisms by which hyperthermia enhances the sensitivity of cells to chemotherapeutic drugs has not yet been elucidated. Methods:To identify the key molecules involved in thermochemotherapy, this study used mass spectrometry (MS)-based quantitative proteomics technology to analyze the effects of thermochemotherapy on the heat-sensitive ovarian cancer cell line A2780. We divided the A2780 cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These synergistic effects increase the susceptibility of tumor cells to cell death. Several studies have reported that proteins or genes such as RBL1 [ 55 ], p53 [ 56 ], Rad51 [ 57 ], and BRCA2 [ 58 ] are involved in DNA repair. Mutations or loss of function of these proteins or genes have been implicated in cancer, and RT + HT has shown an inhibitory effect on cancer proliferation by regulating these factors.…”
Section: Physiological Changes Induced By Rt + Htmentioning
confidence: 99%
“…These synergistic effects increase the susceptibility of tumor cells to cell death. Several studies have reported that proteins or genes such as RBL1 [ 55 ], p53 [ 56 ], Rad51 [ 57 ], and BRCA2 [ 58 ] are involved in DNA repair. Mutations or loss of function of these proteins or genes have been implicated in cancer, and RT + HT has shown an inhibitory effect on cancer proliferation by regulating these factors.…”
Section: Physiological Changes Induced By Rt + Htmentioning
confidence: 99%
“…The recognized biological effects of heat stress include the inhibition of DNA damage repair through protein inactivation or denaturation, raised drug delivery owing to heat‐induced upsurges in blood flow and vascular permeability, and augmented cellular uptake (Singh et al, 2020). A rise in the direct cytotoxicity of the drug have all been linked to this enhanced response in which antitumor agents are potentiated by hyperthermia leading to overwhelming drug resistance (Ni et al, 2022; Salvador et al, 2021). The technique produces thermal energy by subjecting magnetic NPs to an alternating magnetic field.…”
Section: Smart Chemo‐delivery Systemsmentioning
confidence: 99%
“…Despite the exact mechanism being unknown, hyperthermia has been shown to cause lethal cell damage [18 ▪▪ ,19 ▪ ,20 ▪ ,21,22]. Using mass spectrometry-based quantitative proteomics to analyze the effects of thermochemotherapy on an ovarian cancer cell line, Ni et al [18 ▪▪ ] showed that ‘hyperthermia mainly affected the DNA damage repair process in heat-sensitive ovarian cancer cells, which enhanced their sensitivity to chemotherapeutic drugs’.…”
Section: Hyperthermia and Pharmacokinetics Of Hyperthermic Intraperit...mentioning
confidence: 99%
“…Despite the exact mechanism being unknown, hyperthermia has been shown to cause lethal cell damage [18 ▪▪ ,19 ▪ ,20 ▪ ,21,22]. Using mass spectrometry-based quantitative proteomics to analyze the effects of thermochemotherapy on an ovarian cancer cell line, Ni et al [18 ▪▪ ] showed that ‘hyperthermia mainly affected the DNA damage repair process in heat-sensitive ovarian cancer cells, which enhanced their sensitivity to chemotherapeutic drugs’. Moukarzel et al [19 ▪ ] obtained normal and tumor samples pre and post-HIPEC treatment with carboplatin in patients with recurrent ovarian cancer and performed RNA sequencing to elucidate the effect of HIPEC on tumor cells.…”
Section: Hyperthermia and Pharmacokinetics Of Hyperthermic Intraperit...mentioning
confidence: 99%